2010
DOI: 10.1111/j.1399-0012.2010.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Ineligibility for renal transplantation: prevalence, causes and survival in a consecutive cohort of 445 patients

Abstract: Little is known about the proportion of renal transplant candidates who are considered ineligible by the transplant center, the reasons of their ineligibility and their survival during dialysis. In this retrospective, single-center study of 445 adult patients referred between 2001 and 2006, 36 (8%) were deemed ineligible for medical contraindications. The leading reason was cardiovascular (CV) (75%), specifically aorto-iliac, and/or limb vessels atheromatosis or calcifications; ischemic heart disease; or a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
1
23
1
Order By: Relevance
“…In our study, about one-third (37%) of facilities reported that >75% of their patients are ineligible for transplantation; however, previous literature from single-center studies estimate ineligibility for kidney transplantation to be <15% (13, 14). The majority of respondents (61.05%) report that they refer <50% of their patients for KTx.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In our study, about one-third (37%) of facilities reported that >75% of their patients are ineligible for transplantation; however, previous literature from single-center studies estimate ineligibility for kidney transplantation to be <15% (13, 14). The majority of respondents (61.05%) report that they refer <50% of their patients for KTx.…”
Section: Discussioncontrasting
confidence: 50%
“…Efforts that help dialysis patients get kidney transplants should also include promotion of living donor transplantation that are not dependent on the availability of the country’s overall low number of deceased donor organs (18). Regardless of donor organ supply or transplant center capacity, all dialysis patients must be informed about all of their treatment options including KTx (4,13). …”
Section: Discussionmentioning
confidence: 99%
“…Ineligibility due to medical contra indications is estimated to be less than 15% in the few single-center studies that have been conducted. 11,12 However, determination of eligibility for transplantation is complex and varies across transplant centers. Although active drug or alcohol abuse, untreated psychiatric conditions, active cancer, systemic infection, and non adherence are common exclusion criteria for transplant surgery, 13 none are permanent conditions that necessarily preclude transplant referral.…”
Section: Discussionmentioning
confidence: 99%
“…Severe VC in the aorto‐iliac arteries has been considered as a relative contra‐indication for kidney transplantation (KTx). It has been found that 43% of all transplant candidates who are considered ineligible is due to VC .…”
Section: Introductionmentioning
confidence: 99%